2018
DOI: 10.1556/2006.7.2018.01
|View full text |Cite
|
Sign up to set email alerts
|

Exercise addiction in adolescents and emerging adults – Validation of a youth version of the Exercise Addiction Inventory

Abstract: BackgroundBehavioral addictions often onset in adolescence and increase the risk of psychological and social problems later in life. The core symptoms of addiction are tolerance, withdrawal symptoms, lack of control, and compulsive occupation with the behavior. Psychometrically validated tools are required for detection and early intervention. Adolescent screening instruments exist for several behavioral addictions including gambling and video gaming addiction but not for exercise addiction. Given recent empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
4
39
0
1
Order By: Relevance
“…It may be positive for fitness center members to focus on looks if it leads to a physically active lifestyle. However, for some, the focus on appearance might lead to a negative attitude towards oneself and make one exercise excessively [3941]. It is therefore reasonable to question whether fitness centers should focus on appearance when marketing and promoting activities at the centers.…”
Section: Discussionmentioning
confidence: 99%
“…It may be positive for fitness center members to focus on looks if it leads to a physically active lifestyle. However, for some, the focus on appearance might lead to a negative attitude towards oneself and make one exercise excessively [3941]. It is therefore reasonable to question whether fitness centers should focus on appearance when marketing and promoting activities at the centers.…”
Section: Discussionmentioning
confidence: 99%
“…19 In young people, prevalence rates based on an equivalent version of this instrument have been estimated at 4% in school athletes, 8.7% in fitness attendees, and 21% in people with eating disorders. 33 Hence it should be born in mind that the current sample mainly focused on exercise that fell short of the full definition of exercise addiction. Nonetheless, this dimensional approach that includes subsyndromal people may provide useful insights into the full range of behaviors and their associations.…”
Section: Discussionmentioning
confidence: 99%
“…19 Our current data do not contradict this previous finding because (i) a onefactor solution would have been reasonable with the current dataset if one focused solely on eigenvalues as the selection criteria; (ii) the majority of variance here was captured within the first extracted factor; and (iii) in some populations, a one-factor solution may be preferred. 33 Hence, depending on the focus of a given study and its purpose, one-or two-factor solutions would both appear reasonable. Nonetheless, we believe that the twofactor solution here revealed some interesting insights in relation to how distinct aspects of problematic exercise may have different associations with quality of life and underlying psychological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Matos et al found that about 30 percent of young English athletes have experienced overtraining [ 59 ]. Given the growing number of primary exercise dependence in children and emerging adults, Lichtenstein et al have developed and validated a version of the Exercise Addiction Inventory for young in order to assess the prevalence and the incidence of this addiction disorder [ 60 ]. This 6-item instrument includes a question concerning the overtraining syndrome as effect of exercise addiction [ 60 ].…”
Section: Recent Papers Regarding Overtraining and Exercise Addictimentioning
confidence: 99%
“…Given the growing number of primary exercise dependence in children and emerging adults, Lichtenstein et al have developed and validated a version of the Exercise Addiction Inventory for young in order to assess the prevalence and the incidence of this addiction disorder [ 60 ]. This 6-item instrument includes a question concerning the overtraining syndrome as effect of exercise addiction [ 60 ]. Indeed, although a sedentary lifestyle is an alarming behavior problem for children and adolescents [ 61 ], overtraining risk among young athletes is high due to the increasing number of competitions and related training sessions in which they participate [ 62 ].…”
Section: Recent Papers Regarding Overtraining and Exercise Addictimentioning
confidence: 99%